INTERFAITH CHILD ADOPTION BASED ON DECISION NUMBER 9/PDT.P/2018/PN.BMS: A HUMAN RIGHTS PERSPECTIVE - Naufal Irsyaad Immaduddien (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2025)
Abstract: This article aims to analyze the phenomenon of interfaith child adoption through Case Number 9/Pdt.P/2018/PN.Bms with a critical perspective on fulfilling the principles of Human Rights (HR) and the Universal Declaration of Human Rights (UDHR). The research employs a normative juridical method focusing on document studies, including legislation, judicial decisions, and related legal documents, to evaluate the justice aspects in cross-religious child adoption cases. Through an in-depth comparison between court decisions, Law Number 39 of 1999 on Human Rights, and UDHR, the research reveals the complexities of legal and humanitarian issues. The primary finding indicates that regulations requiring child adoption within the same religion potentially nullify fundamental rights guaranteed by human rights instruments. The implications of these restrictions are not merely administrative, but deeply touch the most fundamental human rights, including the right to life, the right to have offspring, the right to justice, and the right to welfare. The research questions the extent to which legal regulations can harmonize positive legal interests with universal humanitarian principles that uphold the dignity of every individual without discrimination. The study concludes that there is a need for a comprehensive review of child adoption regulations that often conflict with human rights protection principles. These rules must be modified to become more humane and inclusive, embracing all parties without discrimination.Absktrak: Artikel ini bertujuan menganalisis fenomena pengangkatan anak beda agama melalui putusan Nomor 9/Pdt.P/2018/PN.Bms dengan perspektif kritis terhadap pemenuhan prinsip-prinsip Hak Asasi Manusia (HAM) dan Deklarasi Universal Hak Asasi Manusia (UDHR). Penelitian menggunakan metode yuridis normatif yang fokus pada studi dokumen, seperti peraturan perundang-undangan, keputusan hakim, dan dokumen hukum terkait, untuk mengevaluasi aspek keadilan dalam kasus pengangkatan anak lintas agama. Melalui komparasi mendalam antara putusan pengadilan, Undang-Undang Nomor 39 Tahun 1999 tentang HAM, dan UDHR, penelitian ini mengungkap kerumitan permasalahan hukum dan kemanusiaan. Temuan utama menunjukkan bahwa regulasi yang mengharuskan pengangkatan anak dalam satu agama berpotensi menggugurkan hak-hak dasar yang dijamin oleh instrumen HAM. Akibat dari pembatasan itu bukan cuma soal administrasi belaka, tapi sampai menyentuh hak-hak dasar kemanusiaan yang paling mendasar, seperti hak untuk hidup, hak melangsungkan keturunan, hak keadilan, dan hak kesejahteraan. Penelitian ini mempertanyakan sejauhmana regulasi mampu menyelaraskan kepentingan hukum positif dengan prinsip-prinsip kemanusiaan universal yang menjunjung tinggi martabat setiap individu tanpa diskriminasi. Penelitian ini menyimpulkan bahwa kita perlu meninjau ulang secara menyeluruh aturan soal pengangkatan anak yang sering bertolak belakang dengan prinsip perlindungan hak asasi manusia. Aturan ini harus diubah agar lebih manusiawi dan bisa merangkul semua pihak tanpa membeda-bedakan.